1970
DOI: 10.3329/ujzru.v26i0.699
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on reproductive performance and productivity of the Black Bengal and Crossbred goat at Atrai, Bangladesh

Abstract: : The present investigation was carried out to detect the status of different productive and reproductive parameters of Black Bengal and Crossbred goats at Bandaikhara village under Atrai Upazilla of Naogaon district during the period of September to December/2005. The average age at first sign of heat of Black Bengal goats was better than that of Crossbred goats. In Black Bengal goat the average age at first kidding was 360.5±10 days, whereas, in crossbred goats it was 411.5±15.5 day. Significantly (P<0.01) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
27
3

Year Published

1970
1970
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 2 publications
16
27
3
Order By: Relevance
“…It was found that sire significantly (P<0.05) affected body weight at ages from birth to the 6th month. This result was supported by Mourad & Anous (1998) and Hassan et al (2007). Dam significantly affected kid body weights only from birth to the 2nd month of age.…”
Section: Resultssupporting
confidence: 72%
“…It was found that sire significantly (P<0.05) affected body weight at ages from birth to the 6th month. This result was supported by Mourad & Anous (1998) and Hassan et al (2007). Dam significantly affected kid body weights only from birth to the 2nd month of age.…”
Section: Resultssupporting
confidence: 72%
“…Rout et al (1999) reported kidding interval was 229.3 ± 26.7 days, which is similar to the present findings. Due to long lactation, the kidding interval (210.6 ± 29.4 days) was longer than in Black Bengal goats (179 ± 20 days) as reported by Hassan et al (2007).…”
Section: Age At First Kidding and Weight Of Dammentioning
confidence: 61%
“…The profitability of goat production depends primarily on the efficiency of female productivity. Improving female's reproductive performance by selection is difficult due to its low heritability (García-Peniche et al 2012) indicating that the possibility for genetic improvement through selection is limited, therefore, crossbreeding can be used to quickly improve reproductive performance via its resultant yield of heterocyst (Hassan et al 2007) and reproductive (Magaña & Correa 2001). However Nguluma et al (2013) reported that crossbreeding did not improve reproduction performance of local goats.…”
Section: Introductionmentioning
confidence: 99%